2016
DOI: 10.1039/c5nr09056c
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characteristics of AlGaN-based three-dimensional hexagonal nanopyramid semi-polar multiple quantum wells

Abstract: We demonstrated for the first time the formation and study of semi-polar AlGaN multiple-quantum-wells (MQWs) grown on highly regular hexagonal AlN nanopyramids. The AlN nanopyramids were obtained by a metal-organic chemical vapor phase deposition regrowth method on a well-ordered AlN nanorod array prepared by a top-down etching process. The growth mechanism of the AlN nanopyramids was ascribed to the slow growth of the (101[combining macron]1) semi-polar plane, which resulted from hydrogen passivation. Beneath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 30 publications
1
27
1
Order By: Relevance
“…Additionally, at 20 mbar, the c ‐plane growth rate is increased which almost leads to a full pyramid with six (10‐11) semi‐polar planes. It is also observed that inclined planes are formed in the upper part of the nanorod sidewalls, which could be associated with ( n 0‐ n ‐1) semipolar crystal planes, where n ≥ 1 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, at 20 mbar, the c ‐plane growth rate is increased which almost leads to a full pyramid with six (10‐11) semi‐polar planes. It is also observed that inclined planes are formed in the upper part of the nanorod sidewalls, which could be associated with ( n 0‐ n ‐1) semipolar crystal planes, where n ≥ 1 …”
Section: Resultsmentioning
confidence: 99%
“…The curved facet evolves between the (0111) plane and the (0112) plane, because (0111) and (0112) are the most energetically favorable planes for the growth of AlGaN and GaN respectively. [45,46] As shown in Figure 1c, it is important to mention that the intensity of the bottom four AlGaN layers is relatively weaker compared with the intensity of the top four AlGaN layers and that the apparent width of the layer is also larger for the bottom InGaN dots than the top ones, all factors which can be explained by the curved nature of the bottom AlGaN layers. Given the complex nature of this heterostructure, it is clear that the combination of APT technique with the information from TEM are the only combined approaches that can reveal this slightly curved nature of the quantum layers and the crystallographic nanosized structure within the heterostructures.…”
Section: Resultsmentioning
confidence: 91%
“…A comprehensive analysis of the polarization effect in an Al 0.5 Ga 0.5 N template has been reported. The calculation results indicated that the piezoelectric polarization field becomes nearly zero for nonpolar and semipolar orientations 31 . Therefore, MQWs grown on the m -plane facet naturally have a high internal quantum efficiency.…”
Section: Resultsmentioning
confidence: 95%
“…This result confirms the previous study of Tian et al . 31 .
Figure 6 TEM images of regrown AlGaN/AlN MQWs.
…”
Section: Resultsmentioning
confidence: 99%